Evaluating and Managing the Microbial Contamination of Eye Drops: A Two-Phase Hospital-Based Study - Léa Roquefeuil; Katia Iskandar; Christine Roques; Loïc Marchin; Mylène Guittard; Hélène Poupet; Marie-Laure Br; Marion Jobard (MDPI AG, 2024)
The microbial contamination of eye drop tips and caps varies between 7.7% and 100%. In seeking patient protection and continuous improvement, the Pharmacy Department in the Sterile Ophthalmological and Oncological Preparations Unit at Cochin Hospital AP-HP, Paris, France, conducted a two-phase study to compare the antimicrobial efficiency and practical use of standard packaging and a marketed eye drop container incorporating a self-decontaminating antimicrobial green technology by Pylote SAS at the tip and cap sites. The first phase was conducted in situ to identify the microbial contaminants of eye drops used in the hospital and community settings. A total of 110 eye drops were included for testing. Staphylococcus species were the most prevalent bacteria. Candida parapsilosis was detected in only one residual content sample and, at the same time, on the cap and tip. The second phase was performed in vitro, according to JIS Z2801. Reductions above one log in Staphylococcus aureus and Pseudomonas aeruginosa counts were noted in Pylote SAS eye drop packaging after 24 h of contact. The practical tests showed satisfactory results. Pylote SAS antimicrobial mineral oxide technology exhibited promising effects that combined effectiveness, safety, and sustainability to protect the patient by preventing infections due to the contamination of eye drop containers.